2021
DOI: 10.23887/jpi-undiksha.v10i4.30328
|View full text |Cite
|
Sign up to set email alerts
|

Internalization of Islamic Values in Developing Students' Actual Morals

Abstract: This study aims to explore the efforts of madrasah teachers to internalize Islamic values in developing students' actual morals. Using a case study research by conducting in-depth interviews with 8 madrasah tsanawiyah teachers and analyzing them with data cleaning, transcripts, coding and categorization, and interpretation. This research resulted in: First, duha sunnah and fardhu prayer in congregation, and get used to respect the teacher, to manage the syahwiya power of students, resulting in "iffah" which ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…Various arguments can explain this situation. First, development of professional teachers can be influenced by the teacher's final understanding, by results of overrating compared to the competence of other professional teaching, and by making analysis of the developing competence ineffective [24], [43], [44]. The lack of development of professional teaching habits and not identifying the developing professional teacher's skills are other possible explanations [41], [43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various arguments can explain this situation. First, development of professional teachers can be influenced by the teacher's final understanding, by results of overrating compared to the competence of other professional teaching, and by making analysis of the developing competence ineffective [24], [43], [44]. The lack of development of professional teaching habits and not identifying the developing professional teacher's skills are other possible explanations [41], [43].…”
Section: Discussionmentioning
confidence: 99%
“…This is where this research's main problem lies, that is, where madrasa teachers' professionalism does not align with standards established in Indonesian laws and regulations [22]. Their performance deviates from the standard even though madrasa teachers possess professional certificates and have received certification allowances [23], [24]. However, facts show that the performance of professional madrasa teachers both in mastery and implementation is still not optimal and requires greater development [22], [23].…”
Section: Introductionmentioning
confidence: 99%
“…Ihsan is a series of Muslim behavior in both physical and mental action. In addition, the practice of Sufism or Sufism also applies to patterns of life accompanied by religious values, for example living in simplicity as a manifestation of the concepts of zuhud and qana'ah (Tambak, et a., 2021). While modern Sufism or in the current context, Sufism emphasizes more on the humanistic, empirical, and functional understanding that can be applied in the behavior of human life (Hamka, 2015).…”
Section: Implementation Of Sufistic Counseling In Overcoming Game Onl...mentioning
confidence: 99%
“…However, the important thing in children's learning assistance is the parents. Prasetyo also revealed that mentoring by parents for children's learning is an effort for parents to accompany, help children's problems during learning, provide motivation, supervise, and provide facilities for children so that children are excited about learning (Tambak et al, 2021).…”
Section: Accompanying Children To Learnmentioning
confidence: 99%